If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4 = -2 + 28 Reorder the terms: 4 + 6x = -2 + 28 Combine like terms: -2 + 28 = 26 4 + 6x = 26 Solving 4 + 6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6x = 26 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 26 + -4 6x = 26 + -4 Combine like terms: 26 + -4 = 22 6x = 22 Divide each side by '6'. x = 3.666666667 Simplifying x = 3.666666667
| 8y-3=3y-2+4y | | 3(4x+5)=7(x-4)+17 | | (2/3)x+(1/6)=(-5/6)x+(5/3) | | 4x+12=3(x+4) | | -56=-4x-2(-7x-2) | | 7(6+x)=6(2-x) | | 328=8(6a+5) | | -5x=-x-12 | | 10x^2-66x+72=0 | | -4x+83=-12x-125 | | 0.5y-2=-.25 | | 10+5(x-2)=4x+1 | | -29=5x-2(3x+10) | | 36x+24=10(x+2+2x) | | 7h-14=42 | | -4-3=0.4x-2y | | -4(x+4)=2(x-10) | | 5g+15=42 | | 314=-x+576 | | -4-3=0.4-2y | | 2(4x+6)=-13+1 | | 3(3z-1)-3(3-2Z)=12 | | x+1=-x+3 | | 19+2(2n-15)=1 | | -4=-3x+5(-x+12) | | Ln(x-4)+ln(x-1)=ln(x-8) | | lnx=-10 | | 2[x+5(6-x)+18]-10=50-10x | | 28=t+24 | | -8(-8+2p)=192 | | 3x-x+6x=17 | | 12c-4=-12c |